Analysis of the influence of the existence of national exams, school origin, and tutoring on mathematics motivation using decision tree - Ma'ulfi Kharis Abadi; Dadan Dasari; Siti Fatimah; Agus Hendriyanto (Universitas Sarjanawiyata Tamansiswa, 2025)
Mathematics is essential as it forms the foundation for sciences applied in the real world. Students' success in learning mathematics is crucial and must be prioritized. To understand and excel in mathematics, diligent study is required. Students who study diligently are often motivated by external factors such as outcomes, targets, environment, and teachers. Enthusiasm serves as the driving force that fosters the desire to learn effectively. Thus, motivation is a critical and consistent factor that encourages students to study diligently, ultimately improving their mathematics learning outcomes. This study examines the influence of school origin, national exams (UN), and tutoring on students' motivation to learn mathematics. The research involves a preliminary study, data collection, and analysis using a decision tree with the help of the Orange application. The results indicate that high motivation levels are more common among students attending public schools and those influenced by the presence of national exams. The findings of this study should be utilized by the government to enhance students' learning motivation and significantly improve mathematics learning outcomes. The study suggests targeted actions, including equitable resource allocation, alternative evaluation systems, teacher training, and enhanced counseling services, to effectively boost students' learning motivation and improve the overall quality of education. This research contributes by providing empirical evidence on the factors influencing students' motivation to learn mathematics, offering insights that can inform policies and interventions aimed at fostering a more effective and engaging learning environment.